Reciprocal Teaching Learning: Is it Effective to Improve Students’ Higher Order Thinking Skills and Scientific Process Skills? - Hidayah, Rofiatul; Latifah, Sri; Komikesari, Happy; Yusuf, Irwan (Indonesian Journal of Science and Mathematics Education, 2021)
This study aimed to measure the effectiveness of using the reciprocal teaching learning model on the higher order thinking skills and science process skills of students. The research method used is a Quasi Experiment. Based on the results of the research calculated by the independent sample t-test from the post-test results of the control class of 66.97 and the experimental class of 77.71, it was obtained tcountmore than ttable (10.167 more than  1.996) and the percentage of observation results from the control class average of 73 and the mean The experimental class average is 76, so that the tcount value is greater than the ttable ((3.656 more than 1.996). Then the effectiveness of the reciprocal teaching model is known through the effect size test and the value of d = 0.5 is obtained. Based on these results, it can be concluded that the reciprocal model This teaching is effective in improving higher order thinking skills and science process skills.